Assessing the validity and reliability of an aggressive behavior scale among health employees (Journal of Academic Research, 2024)
This study aims to assess the validity and reliability of the measure of aggressive behavior among health employees in the city of Misrata. The validity and reliability of one of the scales developed by Neuman and Baron 1998 was tested in the classification of aggressive behavior in the work environment, which consists of three dimensions: expressions of hostility, obstructionism, and overt aggression. Data was collected from employees of public and private hospitals and medical centers located in the city of Misrata from a random sample of (158) participants. Factor analysis was calculated through exploratory factor analysis on the items of the scale according to Principles Components method with oblique rotation using the Statistical Package of Social Sciences SPSS V. 25. The statistical program SPSS AMOS V25. was also used in conducting confirmatory factor analysis through Structural Equation Modeling (SEM). Maximum Likelihood Method was used to infer the validity of the scale and the Cronbach alpha test was used to confirm the reliability of the scale. The results confirmed the validity of the scale in its three dimensions to measure aggressive behavior in the study environment as stated in its original version. According to Likert's five-dimensional scale, the order of the dimensions of aggressive behavior was as follows: expressions of hostility followed by obstructionism and then overt aggression. I recommend more validity and reliability studies to enhance the validity of international standards in the Arab study environment.